GERAKAN MASYARAKAT MADANI DALAM LAKON-LAKON WAYANG KULIT BALI: SEBUAH PERJUANGAN MASYARAKAT YANG TERHEGEMONI (Civil Society Movement in Balinese Leather Puppet Plays Bali: A Struggle of Hegemonized Society) - I Made Budiasa (SALINGKA, 2014)
Appreciation of the literary treasures of the archipelago were removed from the oral literature, especially the play Balineseshadow puppets (LWKB) is an appreciation, preservation, andattempts to document the work of the puppeteer in Bali in his work as a puppet artist. Mastermind as a director and as an actor takoh the language game is able to package the show to be interesting and load with a moral message. As a literary work, LWKB the inner dynamics of the puppeteer hidden inside various problems, such as social criticism, the norms that must be adhered to in the community, and matters relating to ethics in the state and nation. The moral is that posed by the puppeteer, such as the loss of the concept of manyamabraya in society, nervous government in solving the various problems facing thenation, a bureaucratic authoritarian hegemony and strengthening civil society, and the culture of corruption, collusion, and  nepotism is a “treat” at any time to be heard, seen, andexperienced by the puppeteer. This phenomenon, recorded and conveyed through dialogues servant figures which is the symbol of civil society.